1967
DOI: 10.1021/jf60153a015
|View full text |Cite
|
Sign up to set email alerts
|

Fate of 2-methyl-2-(methylthio)propionaldehyde O-(methylcarbamoyl)oxime (Temik) in cotton plants and soil

Abstract: In the cotton plant, Temik [10% granular formulation of UC-21149, 2-methyl-2-(methylthio)propionaldehyde 0-(methylcarbamoyl)oxime] was rapidly metabolized to its sulfinyl derivative (Temiksulfoxide); further oxidation to the sulfonyl compound (Temik-sulfone) was slow. No evidence of oxidative A-demethylation was found. The sulfinyl derivative was degraded primarily by hydrolysis to a sulfinyl-oxime. Both Temik-sulfoxide and Temik-sulfone were stable in cotton. Relatively large amounts of radioactivity were los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
42
1

Year Published

1968
1968
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 11 publications
17
42
1
Order By: Relevance
“…Similar to the degradation patterns of some órgano sulfur pesticides such as aldicarb (Bromilow et al, 1980;Coppedge et al, 1967;Ou et al, 1985;Smelt et al, 1978) and phorate (Talekar et al, 1977;Walter-Echols and Lichtenstein, 1978), we found that P in Arredondo sand was rapidly oxidized to PSO which was further oxidized to PSO. (Figure 2).…”
Section: Because Of Low Levels Of Extractable C Remaining In Arredondsupporting
confidence: 68%
“…Similar to the degradation patterns of some órgano sulfur pesticides such as aldicarb (Bromilow et al, 1980;Coppedge et al, 1967;Ou et al, 1985;Smelt et al, 1978) and phorate (Talekar et al, 1977;Walter-Echols and Lichtenstein, 1978), we found that P in Arredondo sand was rapidly oxidized to PSO which was further oxidized to PSO. (Figure 2).…”
Section: Because Of Low Levels Of Extractable C Remaining In Arredondsupporting
confidence: 68%
“…Flasks were capped with Parafilm. At O, 4,8,12,16, and 30 days the soils were thoroughly mixed and a 10-g sample removed for analysis.…”
Section: Nitrification In Soilmentioning
confidence: 99%
“…The behaviour of aldicarb and its insecticidal metabolites has been studied in a number of plants including: alfalfa Downloaded by [University of California, San Diego] at 14:20 29 June 2016 (Halfhill and Maitland 1973), beans (Skrentny and Ellis 1970), citrus (Iwata et al 1977, Pico et al 1990), conifers (Kearby et al 1970), cotton (Metcalf et al 1966, Coppedge et al 1967, Bull 1968, Ridgway et al 1968, Bartley et al-1970, Andrawes et al 1973, Woodham et al 1973, Aharonson et al-1984, grapes (Hafez andRaski 1981, Krause et al 1986), hops (Sites and Cone 1989), lettuce (Krueger et al 1973), peaches and plums (Klein et al 1984), potatoes (Andrawes et al 1971, Bromilow 1973, George et al-1975, Smelt et al 1977, Wyman et al 1985, Kathpal et al 1988) and sugar beets (Jamet et al 1979, Steele 1979, Rouchaud et al 1980a, 1980b, Dejonckheere et al 1982, Bayoumi and Dreze 1984. In general, the sulfoxide and sulfone metabolites are the major persistent toxicants in foliage while the parent material either disappears rapidly or is not accumulated.…”
Section: Introductionmentioning
confidence: 99%